2019
DOI: 10.1017/dsi.2019.402
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Sound of Electric Vehicles According to Unpleasantness and Detectability

Abstract: Electric Vehicles (EVs) are very quite at low speed, which can be hazardous for pedestrians. It is necessary to add warning sounds but this can represent an annoyance if they are poorly designed. On the other hand, they can be not enough detectable because of the masking effect due to the background noise. In this paper, we propose a method for the design of EV sounds that takes into account in the same time detectability and unpleasantness. It is based on user tests and implements Interactive Genetic Algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In Petiot, Legeay & Lagrange (2019), a study using an IGA for the design of QV sounds was presented. After a definition of the experimental protocol for the listening tests and the sound synthesis technique, a mono-objective optimisation using IGA was implemented, to explore the trade-off between detectability and unpleasantness, which were aggregated as a weighted sum.…”
Section: Introductionmentioning
confidence: 99%
“…In Petiot, Legeay & Lagrange (2019), a study using an IGA for the design of QV sounds was presented. After a definition of the experimental protocol for the listening tests and the sound synthesis technique, a mono-objective optimisation using IGA was implemented, to explore the trade-off between detectability and unpleasantness, which were aggregated as a weighted sum.…”
Section: Introductionmentioning
confidence: 99%
“…Subtle perceptual phenomenon can then be taken into account for the optimization of products involving sensory constraints (Wakefield et al, 2005). A study using IGA for the design of sounds for Electric Vehicles can be found in (Petiot, Legeay & Lagrange, 2019), where an exploration of the tradeoff between detectability and unpleasantness of the sounds is proposed, showing the efficiency of the approach. The present chapter is in the continuity of this work.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies are based on hearing tests of a predefined set of sound stimuli. In a previous paper (Petiot et al, 2019), we proposed a method based on an Interactive Genetic Algorithm (IGA) for the design of EV sounds that takes into account in the same time detectability and unpleasantness. Based on listening tests and a parametric synthesis of EV sounds, it provided efficient solutions, validating the relevance of the approach.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this section is to make a summary of the EV sounds synthesis method, the scenario for the assessment of the detectability and the unpleasantness, and the IGA implementation. For more information, the reader is invited to read the initial paper (Petiot et al, 2019).…”
Section: Introductionmentioning
confidence: 99%